Storage potential of peeled crambe for oil quality - Santos, Silas da S.; Biaggioni, Marco A.M. [UNESP]; Monteiro, Iara M.C. [UNESP]; Sartori, Maria M.P. [UNESP]; Brandão, Fernando J.B. (FapUNIFESP (SciELO), 2019)
Peeling of crambe fruits, besides increasing the yield of mechanical oil extraction, can increase its apparent specific mass from about 330 to 700 kgm-3, reducing transport and storage operating costs, as well as increasing cake protein content. However, there is no information on the quality of the oil extracted from the stored unpeeled crambe. This study aimed to assess the possible effects of peeling fruits submitted to different storage systems. For nine months, peeled and unpeeled crambe fruits were stored in conventional (permeable) and hermetic packages and water content, fatty acid, and acidity and oil peroxide indices were monitored. The experimental design was a completely randomized design in a 2 × 2 × 3triple factorial, with three replications. After analysis of variance, the mean data were compared by the Tukey's test, being considered significant when p < 0.05. The results showed that peeled crambe had better conservation in relation to that unpeeled, mainly when submitted to the hermetic storage system.
Keywords: Biodiesel; Biofuel; Hermetic storage; Oilseeds